Retrospective Longitudinal Survey on Canine Vector-Borne Pathogens: Trends and Challenges of 10 Years of Activities of a Veterinary Blood Bank - Giulia Morganti; Arianna Miglio; Iolanda Moretta; Ambra L. Misia; Giulia Rigamonti; Valentina Cremonini; Maria T. Antognoni; Fabrizia Veronesi (Veterinary Sciences, 2022)
Canine vector-borne pathogens (CVBPs) represent a challenge for veterinary transfusion medicine, since some can be transmitted by blood transfusion and are of zoonotic concern. Epidemiological data on CVBPs, obtained during 10 years of pre-donor screening (2012–2021) by a veterinary blood bank in central Italy, were used to conduct a retrospective epidemiological longitudinal survey. The results were obtained using the Immunofluorescent Antibody Test (IFAT) conducted on sera in order to assess IgG antibodies against Leishmania infantum, Ehrlichia canis, Anaplasma phagocythophilum, Babesia canis, and Rickettsia conorii; the modified Knott’s test and an ELISA kit were used to detect Dirofilaria immitis and Dirofilaria repens. In total, 324 out of the 1260 canine blood donors (25.71%) tested seropositive for at least one pathogen. The highest overall positive rate was detected for L. infantum (12.22%), followed by E. canis (2.30%), A. phagocytophilum (1.19%), D. repens (0.95%), D. immitis (0.32%), and B. canis (0.16%). From 2012 to 2014, a prevalence of 20.12% was recorded for R. conorii. Mixed infections were recorded in 21 dogs. For all the CVBPs investigated, significant differences (p < 0.05) were not observed over the period studied. The results evidenced a non-negligible prevalence of CVBPs in canine donors, which were selected based on strict criteria concerning regular endo- and ectoparasite controls. The results confirmed that the blood bank could be a reliable local epidemiological observatory. The need for implemented screening is discussed.